Seeing gender : an illustrated guide to identity and expression - Gottlieb, Iris (Chronicle Books, 2022)
Essays accompanied by illustrations discuss historic and modern views on gender and sexuality, and profile individuals who have helped shaped the gender-fluid movement. Includes an index.